Validitas Modul Pembelajaran IPA Berbasis Integral Islam dan Sains pada Materi Zat Adiktif Kelas VII MTs Negeri 4 Kerinci: Validity of the Integral Islamic and Science Based Science Learning Module on Addictive Substance Material for Class VII MTs Negeri 4 Kerinci - Dena Yumera; Emayulia Sastria; Lia Angela; Dharma Ferry; Anggi Desviana Siregar; suhaimi (PUAN INDONESIA, 2024)
This research aims to develop a science learning model based on Integral Islam and Science on addictive substance material that is valid and practical. This type of research is development research with a 4D model consisting of Define, Design, Develop and Disseminate. The research population is students of MTS Negeri 4 Kerinci and research samples for class VIII MTs Negeri 4 Kerinci. The data collection technique is a questionnaire. Data analysis in this research is a test of validity and practicality. The results of the research concluded: 1) The Islamic and Science-based science module on addictive substance material was validated by media experts with a final percentage of 83% in the very valid category, validation of the material with a final percentage of 85% in the very valid category and validation of the language aspect obtained a percentage of 88 % in the very valid categor..